THE IMPACT OF GLOBAL WARMING ON THE PUBLIC HEALTH INCREASING THE BACTERIAL CAUSING INFECTIOUS DISEASES PERFORMED BY EXPERIMENT: VECTOR-BORNE DISEASES INSECTS, TAIF, KSA - Sabra, Sherifa Mostafa M.; Ahamed, Samar (International Journal of Research -GRANTHAALAYAH, 2017)
The search conducted on "The impact of global warming (GW) on the public health (PH) increasing the bacterial causing infectious diseases (IDs) performed by experiment: Vector-borne diseases (VBDs) insects, Taif, KSA", the experiment used ants (Taif Tapinoma sessile), prepared, arranged appropriate nests and adjusted the temperature at (20, 25, 30, 35, 40 and 45°C), for a week of each zone. It revealed the behaviour as (normal, semi-normal and ab-normal), the mean of mortality rates were between (0-53.3%). The bacterial contents measured by the turbidity indicated the presence of multiplication, were between (0.109-0.328). The bacterial growth degrees by sings were between (+ - +++++) and percent between (12-100%). Colony Forming Unit/ml (CFU/ml) confined between (1.8X102-15.0X102)/mL. Through this experiment it turned out the GW had a significant role on the PH, helped the proliferation of bacterial pathogens that caused IDS. The conclusion wiped from the experiment that the extent degrees of GW disadvantages on the PH. The PH workers must take the "Preventive Health Prophylaxis Measures" (PHPMs) to protect the individuals from IDs by eliminating the VBDs of various types, monitoring the immunological situation of individuals, provided the vaccinations of IDs and preparing for complete PHPMs against any changes in the PH.